Framing the futures of animal-free dairy: Using focus groups to explore early-adopter perceptions of the precision fermentation process - Broad, Garrett M.; Zollman Thomas, Oscar; Dillard, Courtney; Bowman, Daniel; Le Roy, Brice (Frontiers in Nutrition, 2022)
This paper reports on the findings from a series of virtual focus groups that explored consumer perceptions of animal-free dairy (AFD), an emerging type of animal product alternative produced using the tools of synthetic biology and precision fermentation. Focus group participants came from an international sample of potential “early adopters.” To stimulate conversation, participants were presented with a series of visual “moodboards” that framed key arguments both in favor of and in opposition to AFD. Three primary thematic clusters emerged from the discussion. The first focused on issues of “process, safety, and regulation,” centered on the general reaction of participants to the concept of AFD, their primary concerns, key questions, and the assurances they would need in order to support its advancement. The second focused on issues of “consumer preferences and priorities,” highlighted by the often complicated, and sometimes outright contradictory, stated consumer interests of the participants. The third focused on issues of “food technology and the future,” wherein participants expressed broader views on the role of food technology in society, generally speaking, and the potential futures of AFD, specifically. The general consensus among participants was a cautious openness to the idea of AFD. Outright opposition to the concept was rare, but so too was unabashed enthusiasm. Instead, respondents had a number of questions about the nature of the technological process, its overall safety and regulatory standards, its potential contributions to individual health and climate change mitigation, as well as its organoleptic qualities and price to consumers. Among the positive frames, claims about animal welfare were deemed the most pertinent and convincing. Among the negative frames, concerns about messing with nature and creating potential health risks to individuals were seen as the strongest arguments against AFD. The findings suggest that the key to AFD’s future as a viable market option will depend in large part on the extent to which it can clearly demonstrate that it is preferable to conventional dairy or its plant-based competitors, particularly in the arena of taste, but also across considerations of health and safety, nutrition, environmental effects, and animal well-being.